Nigeria and Ethiopian Diaspora remittances; engagement, policy reforms and poverty reduction. (4th May 2022) - Welde, Tadelech Bubamo; Emovwodo, Silas Oghenemaro; Saud, Muhammad; Wardhani, Baiq Lekar Sinayang Wahyu
ABSTRACT: Diasporas are transnational actors that could be involved in playing a key role to amplify sustainable development in developing countries like Nigeria and Ethiopia. The present study was conducted to explore the potential role of the Nigerian and Ethiopian Diasporas in the process of fostering ongoing economic development in their countries of origin. The article is attempted to highlight: 1) the potential engagements of Nigerian and Ethiopian diasporas contribution to the economic progress and poverty reduction and the significant role of their remittances to accelerate economic growth, (2) the major initiatives taken by the Ethiopian government to attract and engage its diasporas, (3) the government's policy reforms to attract diaspora and (4) the circumstances hampering diasporas potential involvement. The current study opted mixed methodology and data collected through secondary sources and questionnaire to evaluate Diasporas roles and their remittances' impacts on Nigerian and Ethiopian economies. Moreover, the study concludes that, institutional and structural weakness of both countries and diaspora identity politics tended to play a great role in hindering the potential engagement of their diaspora to their countries' development. The study suggests some policy recommendations for the Nigerian and Ethiopian government.